L’esperienza di ISMAR-CNR in Adriatico, Un approccio a lungo termine per la comprensione dei cambiamenti climatici - Marini, Mauro; Ravaioli, Mariangela; Raicich, Fabio; Focaccia, Paola; Trincardi, Fabio (GEOmedia, 2009)
Variability of the oceanographic structure in the Adriaticb Sea and the its relation to climate change: the activity of ISMAR-CNR. Over the last few decades, ISMAR-CNR carried out several oceanographic studies in the Adriatic sea using research vessels, buoys, moored instrumentations and satellite remote sensing for earth exploration and climate change interpretation. The present paper describe the activities of ISMAR-CNR finalized to the answering of key scientific questions and defines the drivers for sea-level rise, eutrophication, hypoxia, and mucilage. In particular, the importance of long term research for spatial and temporal observations of semienclosed marine basins as a key environment for the earth system as a whole is highlited.